The Application of A Simple Ice Cream Experiment to Improve The Understanding of The Students' Concepts of SDN 3 Sawahan on The Changing Form of Objects - Anjani, Reni Dwi; Khoiro, Muhimmatul (Journal of Dedication in Community, 2023)
Teaching without using learning media makes it difficult for students to understand knowledge. This is because students only listen to explanations from the teacher theoretically without any direct learning experience. As a result, the student's understanding of a material tends to be lower. This research was conducted to increase students' conceptual understanding of SDN 3 Sawahan on changes in the shape of objects through a simple ice cream experiment. This study uses qualitative methods with data collection techniques through questionnaires and documentation. The subjects in this study were students in grades 4, 5, and 6 from SDN 3 Sawahan, with a total of 55. The data obtained were analyzed using percentages and diagrams to determine the level of students' understanding of concepts. The results showed that most students understood the concept of changing the shape of objects through a simple ice cream experiment. Students tend to more easily understand concepts in a material through a direct experience such as experiments.